Pengaruh Corporate Governance terhadap Efektifitas Mekanisme Pengurang Masalah Agensi - Zaenal Arifin; Nina Rachmawati (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
The main objective of this research is to investigate whether there are a significant influence between corporate governance and effectiveness of agency-problem-reducing mechanism. The corporate governance is concern on all stakeholder interest while the agency variables are concern only on one of the most important stakeholders’ that is the stockholders. In theory, there should be a significant relationship between the corporate governance and the effectiveness of agency-problem-reducing mechanism. Using all manufacturing companies listed in Jakarta Stock Exchange during 2001 - 2004, this research found that corporate governance influence the effectiveness of debt mechanism in reducing agency problem. The other mechanism, dividend and independent board of director, do not effective to reduce agency problem and the corporate governance does not influence the effectiveness of these two mechanisms. Key words: agency problem, corporate governance, dividend, debt, independent Board of director